Performance enhancement of DCMLI fed DTC-PMSM drive in electric vehicle - Rakesh G. Shriwastava; Mohan P. Thakare; Kishor Vinayak Bhadane; Mahesh S. Harne; Nandkumar B. Wagh (Institute of Advanced Engineering and Science, 2022)
This paper focus on the simulation and hardware analysis of a diode clamped multilevel inverter (DCMLI) fed direct torque control (DTC) permanent magnet synchronous motor (PMSM) drive in electric vehicle (EV) application. DTC-PMSM drive is more used for torque and speed control. The existing DTC PMSM drive consists of torque and flux hysteresis comparators and suffers from variable switching frequency and torque ripples. These problems can be solved by using carrier-based space vector modulation (CBSVM) about torque and flux. In this proposed approach a DCMLI fed 4 poles, 0.5 HP DTC PMSM drive system is designed and simulated using carrier-based CBSVM. Simulation and experimental implementation are carried out in MATLAB environment and AVR Microcontroller respectively. The simulated performances are studied in steady-state and transient conditions for varying load, speed, and torque. The results of the DTC-PMSM drive system using CBSVM show that the proposed method can effectively reduce the torque ripple and maintain a constant speed and also improved driving performance of drive for electric vehicle applications.